PEMASYARAKATAN NARAPIDANA LANSIA : INKLUSI SOSIAL DAN KUALITAS HIDUP YANG LEBIH BAIK - Hukama, Karan Ibra; Subroto, Mitro (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This article explains the importance of considering older prisoners in the context of correctional systems that tend to be dominated by younger populations. Elderly prison populations are growing around the world, and they are faced with unique and complex challenges. Amidst weakening physical conditions and increased medical care needs, elderly prisoners often face social isolation that can undermine their quality of life. This article presents a comprehensive review of the correctionalization of elderly prisoners, delving into the problems they face and the solutions that can be implemented to improve their social inclusion and quality of life. By understanding these challenges and taking appropriate action, we can help elderly prisoners lead more meaningful lives, even within the harsh prison environment. Keywords: Prisoners; Elderly; Inclusion